To the Analysis of the Reliability of Structures of Beam Systems - Ashot G. Tamrazyan (Железобетонные конструкции)
The article discusses the issues of reliability for various types of failures of beam systems. A single-span bending beam is analyzed. The limit state functions for moment failure modes in the characteristic sections of the beam are determined. The ways of forming a plastic hinge for a beam are shown. The lower and upper limits of the beam reliability are calculated. Limit state functions corresponding to failure mechanisms are presented.